The Use of British Parliamentary Debate Style in Teaching Speaking Skill - Nasriandi Nasriandi; Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2021)
This research attempts to discover the Efficiency of using British parliamentary debate style in teaching speaking skill. The problem statement of this research is: is the British Parliamentary debate style effective in teaching Speaking skill at the second and fourth Semester Students of English Study Program IAIN Palopo?, The population of this research is the Second and fourth semester students of English Department of IAIN Palopo who joined the IPEDS( IAIN Palopo English Debate Society).The sample Was taken by using purposive sampling, Based on the students’ interest and allocated time for this research. The number of sample were 15 students. This research used pre-experimental method with pretest and posttest design. The pretest given to know the basic ability of the students in speaking skill and the posttest given to know the students’ improvement in speaking skill after given the treatment, and the researcher used British parliamentary debate style. The result of this research shows that there are significant improvements on students’ speaking skill after conducting the treatments. The result of data analysis shows that ttest (7,829) was higher than ttable (2.093). It indicated that British parliamentary debate style is effective to improve students’ speaking skill at the second and forth Semester of English Study Program IAIN Palopo.